2019
DOI: 10.3390/nano9091345
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic Nanoclusters Coated with Albumin, Casein, and Gelatin: Size Tuning, Relaxivity, Stability, Protein Corona, and Application in Nuclear Magnetic Resonance Immunoassay

Abstract: The surface functionalization of magnetic nanoparticles improves their physicochemical properties and applicability in biomedicine. Natural polymers, including proteins, are prospective coatings capable of increasing the stability, biocompatibility, and transverse relaxivity (r2) of magnetic nanoparticles. In this work, we functionalized the nanoclusters of carbon-coated iron nanoparticles with four proteins: bovine serum albumin, casein, and gelatins A and B, and we conducted a comprehensive comparative study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 89 publications
0
19
0
Order By: Relevance
“…Water soluble casein was prepared as per the procedure mentioned by Khramtsov et al [ 36 ] by adding casein powder to 1M NaOH to prepare 5% ( w/w ) suspension. The mixture was stirred overnight at ~100 rpm in a beaker to obtain a transparent solution.…”
Section: Experimental Methodologymentioning
confidence: 99%
“…Water soluble casein was prepared as per the procedure mentioned by Khramtsov et al [ 36 ] by adding casein powder to 1M NaOH to prepare 5% ( w/w ) suspension. The mixture was stirred overnight at ~100 rpm in a beaker to obtain a transparent solution.…”
Section: Experimental Methodologymentioning
confidence: 99%
“…By employing a rodent model of diet-induced obesity and metabolic syndrome, the authors demonstrated the ability of carnosinol to dose-dependently attenuate 4-hydroxynonenal adduct formation in liver and skeletal muscle, while simultaneously mitigating inflammation, dyslipidemia, insulin resistance, and steatohepatitis. As described by Grasso et al [ 136 ], alternative approaches to increase carnosine delivery and its bioavailability include the use of carnosine derivatives [ 137 , 138 , 139 ]; vesicular systems (nanoliposomes, niosomes, and polymerosomes) [ 140 , 141 , 142 , 143 ]; and nanoparticulate systems [ 144 , 145 , 146 , 147 ]. The currently “under-used” intranasal administration route might also represent an innovative approach, since it can purportedly bypass the BBB and first-pass metabolism [ 148 , 149 ]; the vasodilatory activity of carnosine [ 150 ] also makes this endogenous dipeptide an attractive candidate for this kind of delivery.…”
Section: In Vivo Preclinical Studies: Administration Route Dosage Tre...mentioning
confidence: 99%
“…In comparison, tannic acid-coated MNPs already formed aggregates at 0.05 M and higher sodium chloride concentration [107]. The albumin-coated nanoparticles size did not alter for a long time in various pH and bioreagents temperature storage range and under 37 • C [26,109,111]. There were no significant changes in blood serum/plasma [26].…”
Section: Albumin Coating Effect On Mnps Water Solution Stability and ...mentioning
confidence: 86%
“…A modern approach is using biomolecules coating for improved biocompatibility [3,12]. Albumin adsorption prevents nucleation and the aggregation of MNPs, increases colloidal stability, and is optimal for the in vivo use of nanoparticles [26,[107][108][109][110][111][112][113][114][115][116]. For example, BSA-coated MNP remained excellent colloidal stability at 0.15 M sodium chloride concentration for more than one week.…”
Section: Albumin Coating Effect On Mnps Water Solution Stability and ...mentioning
confidence: 99%
See 1 more Smart Citation